Self-polymerization of dopamine-coated zinc oxide as a potential antibacterial nanoparticle with molecular docking analysis - Albarqouni, Yasin M.Y.; Roney, Miah; Chong, Kwok Feng; Thalji, Mohammad R.; Najafi, Gholamhassan; Arman, Abdullah (Springer Berlin Heidelberg, 2025)
The escalating prevalence of multidrug-resistant bacteria on medical surfaces necessitates the development of innovative antibacterial strategies. In this study, we report synthesizing and evaluating zinc oxide nanoparticles functionalized with polydopamine (ZnO/PDA) as a potent antibacterial agent, exhibiting notable efficacy at a low concentration of 5 mg/mL. Structural and morphological analyses confirm the successful surface decoration of ZnO with PDA, yielding a distinctive popcorn-like architecture that facilitates bacterial growth inhibition. Antibacterial assays conducted against Bacillus cereus (Gram-positive) and Escherichia coli (Gram-negative) demonstrate superior activity against both strains, outperforming previously reported ZnO-based systems. Hemocompatibility assessments reveal excellent blood compatibility, with a hemolysis rate of only 1.13%, underscoring the nanocomposite's potential for biomedical applications. To probe molecular interactions, in-silico docking studies are performed targeting key virulence proteins: Q81BN2_BACCR from B. cereus and DHOase from E. coli. The ZnO/PDA nanocomposite exhibits strong binding affinities, with docking energies of −10.3 kcal/mol and −8.4 kcal/mol, respectively, surpassing those of clindamycin, a clinically used antibiotic. The antibacterial activity of ZnO/PDA is likely mediated through multiple mechanisms, including; direct physical disruption of the bacterial membrane by its nanostructure and molecular-level interference via protein binding and generation of reactive oxygen species (ROS) by ZnO may further contribute to microbial inactivation. While this study primarily evaluates antibacterial efficacy, integrating biocompatibility, structural robustness, and scalable synthesis highlights the promise of ZnO/PDA nanocomposite for next-generation antimicrobial coatings. Future prioritizes comprehensive cytotoxicity assessments and mechanistic studies to advance clinical translation.